PERANAN MANAJEMEN INOVASI DALAM MENINGKATKAN KINERJA ORGANISASI PENDIDIKAN - Siti Nurjanah (Conference In Business, Accounting, And Management (CBAM), 2015)
The competition of education organization is marked with the emergence various new organization and the advancement of technology that accompany the competition business. Innovation management needed each organization to face changes and global competition. Management are currently running is a scientific-based  management  is  still  temporary,  thus  requiring  innovation  to  achieve  competitive advantage of the company.   Innovation that can be done in service organizations is to create new business model, developing new services, a new user interface and make innovation administration. Innovation realized when it is supported by creativity, knowledge, but the competencies and the need of community.  Keywords: innovation, creativity, knowledge